Techno-ökonomische Bewertung der Produktion regenerativer synthetischer Kraftstoffe - Paul Heinzmann; Simon Glöser-Chahoud; Nicolaus Dahmen; Uwe Langenmayr; Frank Schultmann (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2021)
Die Emissionen des Mobilitätssektors basieren derzeit maßgeblich auf der Nutzung fossiler flüssiger Energieträger . Trotz zunehmender Elektrifizierung, spielen flüssige und gasförmige Kraftstoffe kurz und mittelfristig noch eine bedeutende Rolle und werden voraussichtlich in einigen Bereichen auch in längerfristiger Zukunft benötigt. Um dennoch eine Minderung der THG Emissionen zu erreichen, stehen mehrere Technologien und Verfahrenskonfigurationen zur Erzeugung regenerativer synthetischer Kraftstoffe zur Verfügung. Im Rahmen einer techno ökonomischen Analyse werden potenzielle Herstellungsverfahren identifiziert, sowie deren charakteristische Merkmale zusammengetragen. Für die anschließende technische Analyse wurde eine Prozesssimulation in Aspen Plus ® erstellt, woraus die Bestimmung charakteristischer technischer Kenngrößen erfolgte. Anhand der Simulationsergebnisse wurde anschließend eine ökonomische Bewertung des Verfahrens durchgeführt . Die Wahl fiel auf ein Power to Liquid Verfahren unter Nutzung von CO 2 Emissionen eines Zementwerks. Die Konversion zu Kraftstoffen erfolgt durch eine Fischer Tropsch Synthese und teilweiser Veredelung in einem Hydrocracking Verfahren in die Zielprodukte einer Diesel und einer Benzinfraktion. Im Rahmen dieser Arbeit wird das beschriebene Verfahren für drei Produktionskapazitäten untersucht. Unter den getroffenen Annahmen beträgt die Kohlenstoffeffizienz der gewählten Prozessroute 92%, der Wasserstoffwirkungsgrad 63%, sowie der energetische Wirkungsgrad 37%. Die spezifischen Herstellungskosten liegen für den Basisfall bei 3,26 exteuro, für eine Anlage geringerer Produktionskapazität bei 3,51 exteuro und für eine Anlage höherer Kapazität bei 3,11 exteuro pro Liter Kraftstoff. Die Kosten der elektrischen Energie und der Investitionsbedarf der PEM Elektrolyse sind dabei die maßgeblichen Kostenfaktoren. – – The advancing global climate change makes it necessary to reduce greenhouse gas (GHG) emissions in all sectors. The mobility sector currently mainly depends on the use of fossil fuels in combustion engines leading to high levels of CO2 emissions. The electrification of some modes of transport (especially in the field of passenger cars and light duty vehicles), in conjunction with the generation of regenerative electrical energy, can significantly reduce CO2 emissions in the transport sector. However, liquid and gaseous fuels will still play an important role in the short and medium term and will also be required in the longer term in some areas of transportation such as aviation, ship or heavy goods transport. In order to achieve a reduction in GHG emissions using combustion engines, several technologies and process configurations are available for the production of regenerative synthetic fuels. In this working paper, we present first results of a techno-economic analysis of synthetic fuel production (e-fuels) based on green hydrogen and CO2. To this end, potential synthesis processes are identified in a preliminary study and their characteristic features are collated. For the subsequent technical analysis, we performed a process simulation in Aspen Plus®, from which characteristic technical parameters were determined. An economic evaluation of the process was then carried out on the basis of the simulation results. Based on the developed technology overview, the choice fell on a power-to-liquid process using CO2 from the exhaust gases of a cement plant. The process can be divided into the sub-processes CO2 separation, hydrogen supply, synthesis gas production, synthesis and product processing. The CO2 is separated from the cement waste gas by means of chemical absorption scrubbing. A PEM electrolysis is used to provide hydrogen. Synthesis gas is obtained by using an rWGS reactor. The energy required for this is provided by the combustion of part of the gaseous product in an oxyfuel burner. The conversion to fuels takes place through a Fischer-Tropsch Synthesis (FTS), the obtained mixture of hydrocarbons is separated into the target products of a diesel and a gasoline fraction through distillation and partial refinement in a hydrocracking process. Within the scope of this thesis, the process described is examined for three production capacities, which are based on typical sizes of German cement works. Under the assumptions made, the carbon efficiency of the selected process route is 92%, the hydrogen efficiency is 63%, and the energetic efficiency 37% based on the lower heating value (LHV). The specific production costs for the base case are exteuro 3.26, for a system with a lower production capacity it is exteuro 3.51 and for a system with a higher capacity it is exteuro 3.11 per liter of fuel. The cost of electrical energy and the investment required for PEM electrolysis are the main cost factors.
Keywords: 330